Implementation of Human Resources Management for Educators in State Madrasah Aliyah in Bandar Lampung City - Two Bagas Akma Hasada; Oki Dermawan; Subandi (Bulletin of Science Education, 2024)
This study aims to 1) Identify and describe the efforts of madrasah management in implementing human resource management of educators and education personnel in directing and managing human resources related to organizing. 2) Identify and describe how the performance of existing educators and education personnel is. 3) Identify and describe the existing promotion and position system. 4) Identify the process and results of assessing educator and education personnel resources. This study uses a qualitative descriptive approach. Data collection was carried out by conducting interviews, observations, and documentation. Data analysis used in this study was carried out by reducing the data, then presented in the form of descriptions, and verified by drawing conclusions. The results of this study indicate that: 1) Organizing educators is very important to achieve the goals that have been set. This organization includes the preparation of a study schedule that is in accordance with the competencies of each teacher 2) Implementation of educator performance is running well. The educator work program includes supervision, assessment, and integrated technology-based training. Evaluation is carried out through annual supervision by the head of the madrasah and related parties, with teacher performance being assessed as good based on the supervision 3) Job promotion and compensation to educators are based on their competence, motivation, and integrity. Rewards are given to teachers who excel as a form of job promotion 4) Implementation of educator assessment at MAN Se-Kota Bandar Lampung has been carried out well and programmed. Assessment is carried out through supervision carried out by the head of the madrasah or a team of senior teachers, with evaluation through filling out forms, student satisfaction surveys, and assessments by the head of the madrasah.